OC-111 Characterisation of t-helper and t-regulatory cells in chronic pancreatitis. (28th May 2012) - Jupp, J; Fine, D; Johnson, C D; Gadola, S
Abstract : Introduction: It is suggested that T-lymphocytes play a role in the pathogenesis of chronic pancreatitis (CP), but little is known about the composition of T-cell subsets in this disease and previous studies have been discordant. 1–4 We therefore aimed to characterise T-helper (Th) and T-regulatory (Treg) lymphocytes in CP tissue and peripheral blood. Methods: Peripheral blood mononuclear cells were isolated from 15 patients with CP (all male, median age 48.2 years) and 14 controls (10 male, four female, median age 56.1 years). Mononuclear cells were also isolated from the pancreatic tissue of four CP patients (all male, median age 41 years) using enzymatic and mechanical digestion, followed by density gradient centrifugation. The mononuclear cells were stimulated with PMA and ionomycin (not Treg cells), and analysed using a FACSAria flow cytometer. Live CD3 + CD4 + Th1, Th2, Th17 and Treg cells were identified as IFN-γ +, IL-13 +, IL-17 + (IFN-γ ± ), and CD25 + FoxP3 + CD127 lo/− respectively. Statistical analysis was performed using a Mann–Whitney U Test. Results: The peripheral blood of CP patients comprised a significantly higher percentage of Th1 cells (15.2% vs 8.11%; p=0.03), Th2 cells (2.00 % vs 1.17%; p=0.03), Th17 cells (1.23% vs 0.41%; p=0.003), dual secreting IFN-γ + IL-17 + Th17 cells (0.11% vs 0.03%; p=0.003) and Treg cells (6.30% vs 4.40%; p=0.05) compared to controls. CP patients who consume excess alcohol have significantly more Th1 cells than non-drinkers (23.7% vs 9.81%; p=0.01). The T-helper cell infiltrate in CP tissue was mainly composed of Th1 cells (26.1%–57.2%, median 41.5%). Th17 cells were also seen (0.95%–3.80%, median 2.1%), including IFN-γ + IL-17 + Th17 cells (0.22%–2.39%, median 0.37%). No discernible Th2 cells were identified and few or no Treg cells were seen in CP tissue. Conclusion: This work is the first to demonstrate a significant increase in the number of Th17 cells in the peripheral blood of CP patients, and to clearly demonstrate that Th1 cells are the principal T-helper cell found in CP tissue along with appreciable numbers of Th17 cells. Interestingly there is no polarisation of the peripheral blood T-helper cell response in CP towards either a Th1 or Th2 phenotype. It appears therefore that the blood of CP patients is primed to respond non-specifically to inflammatory stimuli. Intriguingly CP patients who consume excess alcohol have more peripheral blood Th1 cells. Alcohol increases gut permeability causing high circulating levels of lipopolysaccharide which is known to generate Th1 cell responses. 5 These combined features may contribute to the pathogenesis of CP. Competing interests: None declared. References: 1. Hunger RE . Gastroenterology 1997. 2. Ebert MP . Am J Gastro 1998. 3. Miyoshi H . Pancreas 2008. 4. Schmitz-Winnenthal H . Gastroenterology 2010. 5. Bode C . J Hepatol 1987.